EMPOWER: Bundled Socio-technical Innovations (STIBs) for Women’s Resilience and Empowerment - Puskur, Ranjitha; Nchanji, Eileen Bogweh (CGIAR Initiative on Gender Equality, 2022)
Significant number of technical innovations exist, but the uptake by women is low. Contextually relevant configurations of combinations of social and technical innovations can help overcome this challenge.